2006
DOI: 10.3319/tao.2006.17.3.533(t)
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nonlinear Site Response Using the H/V Spectral Ratio Method

Abstract: ABSTRACT1 Institute of Geophysics, National Central University, Chung-Li, Taiwan, ROC 2 National Center for Research on Earthquake Engineering, Taipei, Taiwan, ROC * Corresponding author address: Prof. Kuo-Liang Wen, Institute of Geophysics, National Central University, Chung-Li, Taiwan, ROC; E-mail: wenkl@earth.ncu.edu.twThe horizontal-to-vertical spectral ratio has become increasingly popular in studies of site effect and determination of the predominant period of a site. In this study, this method is extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…The effects of soil nonlinearity on observed ground motions at free-surface have also been reported [6,[16][17][18]. For example, Wen and others [17] and Nagashima and others [18] showed the effects of soil nonlinearity on the horizontal-to-vertical spectral ratio (HVSR) of the observed ground motions.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The effects of soil nonlinearity on observed ground motions at free-surface have also been reported [6,[16][17][18]. For example, Wen and others [17] and Nagashima and others [18] showed the effects of soil nonlinearity on the horizontal-to-vertical spectral ratio (HVSR) of the observed ground motions.…”
Section: Introductionmentioning
confidence: 88%
“…For example, Wen and others [17] and Nagashima and others [18] showed the effects of soil nonlinearity on the horizontal-to-vertical spectral ratio (HVSR) of the observed ground motions. Even quantitative simulation of waveforms based on strong and weak motions has been studied by some researchers [19,20].…”
Section: Introductionmentioning
confidence: 97%
“…They pointed out that the nonlinear character of the response appeared for at least 3 h after the main shock even for weak motions (∼20 cm/s 2 ); that is, the permanence in the liquefaction state. Wen et al (2006) applied the S-H/V ratio technique to the same data used in Aguirre and Irikura (1997) and obtained consistent results.…”
Section: Nonlinear Site Effectmentioning
confidence: 61%
“…The S-H/V ratio is useful for detecting the nonlinear site effect, because it needs no reference site. In practice, Wen et al (2006) proposed a technique for identifying the nonlinear site response using the S-H/V ratio of surface records at a single station. They demonstrated that the S-H/V ratio for strong motion data with the nonlinear response, which has been identified using vertical array data, shows the dominant period shift to longer period and the lower ratio level at short periods in comparison with the S-H/V ratio for weak motion data with the linear response.…”
Section: Nonlinear Site Effectmentioning
confidence: 99%
“…Lachet and Bard (1994) and Dravinski et al (1996) also showed through theoretical study that the horizontal-to-vertical (H/V) spectral ratio can show the dominant frequency at a site. Wen et al (2006) used the H/V spectral ratio to identify nonlinear soil response. Figure 7 plots the H/V spectral ratio of these events.…”
Section: Frequency Domain Analysismentioning
confidence: 99%